PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA SEKOLAH MENENGAH ATAS DENGAN MODEL DISCOVERY LEARNING - Mirunnisa (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
Mathematics has an important role in the development of science, because mathematics is a science with regard to ideas, structures and relationships are arranged logically associated with abstract concepts. Students will understand the mathematical concepts when students have high mathematical reasoning abilities. But in reality the reasoning skills of students is still relatively low. Reasoning skills students can be grown if students are given the opportunity to rediscover the mathematical concepts learned. One model of learning that can improve the ability of reasoning is discovery learning, because this model will help the students to understand and analyze the decision-making process in its findings. This study aims to: 1) determine an increase in the ability of mathematical reasoning with models of discovery learning, 2) understand the interaction between learning models and grouping of students to increase the ability of mathematical reasoning. This study was an experimental study with pretest-posttest study design group design. The study population throughout the class X SMA Negeri 1 Peukan Pidie with samples of class X 5 (experimental class) and class X 4 (control group). The data collection was done by using reasoning ability tests. Data were analyzed using ANOVA two lanes with α = 5%. Based on the results of data analysis can be concluded that: 1) increase the ability of students taught mathematical reasoning with models of discovery learning is better than being taught by conventional. 2) there is no interaction between the learning model and student level to the improvement of mathematical reasoning abilities. Abstrak Matematika memiliki peranan penting dalam perkembangan ilmu pengetahuan, karena matematika merupakan ilmu yang berkenaan dengan ide-ide, struktur-struktur dan hubungan-hubungan yang secara logis yang berkaitan dengan konsep-konsep yang abstrak. Siswa akan lebih dapat meningkat memahami matematika apabila siswa telah mempunyai kemampuan penalaran matematis. Namun kenyataannya kemampuan penalaran siswa masih tergolong rendah. Salah satu model yang dapat meningkatkan kemampuan penalaran siswa adalah model discovery learning. Penalaran siswa dapat ditumbuhkan jika siswa aktif dalam kegiatan menemukan kembali konsep sehingga dapat memotivasi siswa dalam belajar. Penelitian ini bertujuan untuk:1) mengetahui peningkatan kemampuan penalaran matematis dengan model discovery learning, 2) mengetahui interaksi antara model pembelajaran dan pengelompokan siswa terhadap peningkatan kemampuan penalaran matematis. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian pretest-postes group design. Populasi penelitian seluruh siswa kelas X SMA Negeri 1 Peukan Pidie dengan sampel kelas X5 (kelas eksperimen) dan kelas X4 (kelas kontrol). Pengumpulan data dilakukan dengan teknik tes. Data yang telah terkumpul kemudian dianalisis dengan menggunakan uji ANAVA dengan α=5%. Berdasarkan hasil analisis dapat disimpulkan bahwa: 1) peningkatan kemampuan penalaran matematis siswa yang diajarkan dengan model discovery learning lebih baik dari pada yang diajarkan dengan konvensional. 2) tidak terdapat interaksi antara model pembelajaran dan level siswa terhadap peningkatan kemampuan penalaran matematis. Kata kunci: Kemampuan penalaran matematis, Model Discovery Learning